KAP Analysis of Nurses Regarding Biochemical Waste Management at Nishtar Hospital, Multan - Anjum, Misbah; Majeed, Shagufta; Zubairy, Moona (Biological and Clinical Sciences Research Journal, 2025)
Effective management of biochemical waste is crucial in preventing hospital-acquired infections and ensuring environmental safety. Nurses play a central role in this process, yet gaps in knowledge, attitude, and practice (KAP) may hinder safe waste disposal. Objective: To assess the knowledge, attitudes, and practices (KAP) regarding biochemical waste management among nurses in a tertiary care hospital. Methods: An analytical cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan, from January 2024 to January 2025. A total of 200 permanently employed nurses were selected using non-probability sampling. Data were collected using a structured questionnaire consisting of 13 knowledge items, 28 attitude items, and 24 practice items. Demographic data included age, gender, job experience, designation, marital status, and departmental assignment. Statistical analysis was performed using SPSS version 25, with associations evaluated using Chi-square tests and p ≤ 0.05 considered significant. Results: Half of the participants (50%) demonstrated unsatisfactory knowledge regarding biochemical waste management, and 90% reported no prior education or training on the topic. Unfavorable attitudes were found in 82% of nurses, and 50% showed poor practices. Nurses aged 30–45 years were more likely to have satisfactory knowledge (80%, p = 0.001). Higher knowledge scores were also observed among nurses in the emergency department (73%, p = 0.03) and maternity ward (90%, p = 0.001). Nurses with over 10 years of experience showed significantly better knowledge (75%) compared to those with less experience (44%). Conclusion: This study revealed a significant deficiency in knowledge, attitudes, and practices related to biochemical waste management among nurses. Targeted training and continuous education programs are crucial for enhancing compliance and maintaining safe healthcare environments.